ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI NIAT PERILAKU PENGGUNA APLIKASI BIBIT DI KOTA SEMARANG - Rifa Alehantaka; Wahyu Meiranto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the factors that influence the behavioral intentions of Bibit application users in Semarang City using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) framework developed by Venkatesh et al. (2012). UTAUT 2 consists of eight main variables: performance expectations, effort expectations, facilitating conditions, habit, perceived value, hedonic motivation, and behavioral intention toward technology use, in this case the Bibit applicationThe study population consists of all active users of the Bibit application in Indonesia, with a sample size of 310 people living in Semarang City. A purposive sampling method was used. Data were collected through an online survey using social media. 31 items were analyzed using the PLS-SEM method with the assistance of SmartPLS 4 software.The results indicate that four hypotheses were accepted. The variables of performance expectations, effort expectations, habits, and hedonic motivation have a significant positive influence on the behavioral intentions of Bibit application users. However, social influence, facilitating conditions, and price value do not influence the behavioral intentions of Bibit application users.